The metabolism of histamine in rat hypothalamus and cortex after reserpine treatment. (June 2015) - Maldonado, Martin; Maeyama, Kazutaka
Highlights: The effect of reserpine on histamine and tele-methilhistamine is analyzed. These results are compared to catecholamines. MAO activity is analyzed after reserpine treatment. HMT activity is analyzed after reserpine treatment. Mast cells deficient rats are used to clarify HA metabolism in HAergic neurons. Abstract: The effect of reserpine on histamine (HA) and tele-methylhistamine ( N τ -MHA) in hypothalamus and cortex of rats was analyzed and compared to catecholamines. IP injection of reserpine (5 mg/kg) confirmed the effectiveness of reserpine treatment on noradrenaline and dopamine levels. Our in-vitro experiment with synaptosomal/crude mitochondrial fraction from hypothalamus and cortex confirmed that while mono amine oxidase (MAO) is an efficient metabolic enzyme for catecholamines, HA is not significantly affected by its enzymatic action. HMT activity after reserpine, pargyline and L-histidine treatment showed no differences compared to the control values. However HDC was significantly increased in both hypothalamus and cortex. In this study, Ws/Ws rats with deficiency of mast cells were used to clarify aspects of HA metabolism in HAergic neurons by eliminating the contribution of mast cells. The irreversible MAO-B inhibitor Pargyline (65 mg/kg) failed to accumulate N τ -MHA in the hypothalamus. However, when animals treated with reserpine and pargyline/reserpine were compared, the last group showed higher N τ -MHA values ( p < 0.01 ). Moreover, the precursor of HA, L-histidine (1 g/kg), produced an increase of HA in the hypothalamus to 166% and the cortex to 348%. In conclusion, our results suggest that the effect of reserpine on the HA pools in the brain might be different. The neuronal HA pools are more resistant to reserpine as compared to those of catecholamine. Moreover, the HAergic pool appears to be more resistant to depletion than mast cells' pool, and thus HDC/HMT activity and its localization may play a key role in the understanding of HA metabolism in brain after reserpine treatment.